Relationship between Feline calicivirus Load, Oral Lesions, and Outcome in Feline Chronic Gingivostomatitis (Caudal Stomatitis): Retrospective Study in 104 Cats - Druet, Isabelle; Hennet, Philippe (Frontiers in Veterinary Science, 2017)
Objective This study was performed to assess the relationship between oral Feline calicivirus (FCV) load and severity of lesions at the time of presentation of cats suffering from feline chronic gingivostomatitis (FCGS) (part 1) and treatment outcome after dental extractions (part 2). We hypothesized that a higher FCV viral load would be positively correlated with the severity of lesions at presentation and negatively correlated with treatment outcome. In addition, the effect of dental extractions on outcome and the influence of preoperative severity of lesions on the outcome were investigated. Materials and methods Cats with FCGS were included in the study if they had been diagnosed with caudal stomatitis, had been tested positive for FCV using a real-time reverse transcriptase-PCR test on oropharyngeal swab, and had dental extractions performed within the authors’ department. General practitioners provided all previous medical treatments. Cats with recheck examinations were included in part 2 of the study. Multivariate statistical analysis was performed to assess the relationship between the different parameters. Results One hundred four cats met the requirements for part 1 and 56 cats for part 2 of the study. Data collected from patients’ record included patient history, viral testing results, extent and severity of oral lesions, extent of teeth extraction. Signalment, history, preoperative treatment, and severity of caudal and alveolar stomatitis score were not associated with FCV load (P > 0.05). Presence of lingual ulcers was significantly correlated with FCV load (P = 0.0325). Clinical cure (32.1%) or very significant improvement (19.6%) was achieved in 51.8% of cats within 38 days. Concomitantly, 60.7% of the owners considered their cat cured (41.1%) or significantly improved (19.6%). Extent of teeth extraction was not found to influence the clinical outcome (P > 0.05). Conclusion The results of this study did not support the hypothesis that FCV oral load is correlated with the severity of oral lesions or with the outcome following dental extractions. In addition, the severity of caudal inflammation was not correlated with healing time or achievement of cure.